Radiation resistivity of Ti-5331 alloy with different microstructures - Zhen Wu; Yunmei Shi; Xudong An; Qianqian Wang; Te Zhu; Qigui Yang; Eryang Lu; Kenichiro Mizohata; Mingpan Wan; Peng Zhang; Baoyi Wang; Xingzhong Cao (Journal of Materials Research and Technology)
Titanium alloys have promising potential for applications in marine nuclear power systems owing to their exceptional mechanical and corrosion properties. Nevertheless, their radiation resistivity is a determining factor for their extensive use as structural materials in nuclear energy systems. In this study, the radiation resistivity of Ti–5Al–3V–3Zr–Cr (Ti-5331) alloys with three different microstructures was examined using a combination of characterization techniques including positron annihilation Doppler broadening spectroscopy (DBS), Elastic Recoil Detection Analysis (ERDA), Transmission Electron Microscope (TEM), Small-Angle X-ray scattering (SAXS) and nanoindentation. The results reveal that the equiaxed structure, bimodal structure, and Widmanstatten structure of Ti-5331 alloy obtained through different annealing processes exhibit differences in the number of interfaces and the content of the β phase. The α/β interfaces can significantly enhance the radiation resistance of titanium alloys by inhibiting the diffusion of helium atoms after helium ion irradiation. Notably, the alloy with a bimodal structure exhibited the best overall radiation resistivity, showing small defect size, low hardening effect, and low swelling rate of 0.003%. Moreover, the size of helium bubbles of the bimodal structure is half of that in the equiaxed structure and Widmanstatten structure. Thus, the bimodal structure of the Ti-5331 alloy possesses superior radiation resistivity.